Supporting learner driven learning in Malaysian higher education / Nor Aziah Alias - Alias, Nor Aziah (UiTM Press, 2019)
Enormous changes are taking place in the 21st century. The fourth industrial revolution termed as Industry 4.0 will definitely change the education landscape and will transform higher education. The internet, cloud computing and the advances in robotics are major game changers that have spurred big data, accessible content, ubiquitous learning, global learning and the Internet of Things. According to Fisk (2017), Education 4.0 is inevitable and among many things.